2022
DOI: 10.1093/plcell/koac344
|View full text |Cite
|
Sign up to set email alerts
|

Different combinations of laccase paralogs nonredundantly control the amount and composition of lignin in specific cell types and cell wall layers in Arabidopsis

Abstract: Vascular plants reinforce the cell walls of the different xylem cell types with lignin phenolic polymers. Distinct lignin chemistries differ between each cell wall layer and each cell type to support their specific functions. Yet the mechanisms controlling the tight spatial localization of specific lignin chemistries remain unclear. Current hypotheses focus on control by monomer biosynthesis and/or export, while cell wall polymerization is viewed as random and non-limiting. Here we show that combinations of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 83 publications
0
31
0
Order By: Relevance
“…For example, AtPRX2 and AtPRX71 prefer the S unit over the G unit for oxidation ( Shigeto et al., 2014 ). Similarly, genetic analysis using multiple LAC mutants brought further support to the idea that lignin deposition is mediated by cell type–specific LACs ( Blaschek et al., 2023 ). Mutation of LAC4 , LAC11 , and LAC17 , which are highly expressed in lignifying tissue, significantly reduced lignin accumulation in stems and roots ( Zhao et al., 2013 ).…”
Section: Lignin Biosynthesismentioning
confidence: 91%
See 3 more Smart Citations
“…For example, AtPRX2 and AtPRX71 prefer the S unit over the G unit for oxidation ( Shigeto et al., 2014 ). Similarly, genetic analysis using multiple LAC mutants brought further support to the idea that lignin deposition is mediated by cell type–specific LACs ( Blaschek et al., 2023 ). Mutation of LAC4 , LAC11 , and LAC17 , which are highly expressed in lignifying tissue, significantly reduced lignin accumulation in stems and roots ( Zhao et al., 2013 ).…”
Section: Lignin Biosynthesismentioning
confidence: 91%
“…It is also worth mentioning that LAC4 , LAC5 , LAC10 , LAC12 , and LAC17 are less important for lignin accumulation in protoxylem than other lignified cell types. Similarly, mutation of the above five LAC s did not affect mechanical strengthening of secondary xylem TEs ( Blaschek et al., 2023 ). These results indicate that additional LAC s are involved in lignin accumulation in protoxylem and secondary xylem.…”
Section: Lignin Biosynthesismentioning
confidence: 97%
See 2 more Smart Citations
“…In GWAS, Chen et al [61] identified GRMZM2G035506 (POD7), which was located near the PZE-105098349 marker and regulated the growth of deep-sowing maize seedlings. Leonard et al [62] proposed that the spatial control of lignin chemistry depends on different combinations of laccase (LAC) with nonredundant activities immobilized in specific cell types and cell wall layers. In this study, we also identified two LAC genes (i.e., GRMZM2G447271 and GRMZM2G336337) in MQTL8-1 region that were annotated to the lignin catabolic process (GO:0046274).…”
Section: Candidate Genes In Major Qtls and Mqtls Regionsmentioning
confidence: 99%